Analisis dan Perancangan Operasional Sistem Berbasiskan CRM (Studi Kasus pada PT Terang Dunia Internusa) - Tanty Oktavia (Bina Nusantara University, 2010)
Article to design an operational system based Customer Relationship Management (CRM) that can connect customers with the company. It is expected that the exchange of information between both parties can be properly channeled, in short, accurate, and actual business-process occurs. Information is an important part in the business cycle because it includes all the transactions that are closely related business activities that occurred. The method used in designing this system is the Object Oriented Analysis and Design. Results to be achieved from this research are the formation of a web-based system that is able to become a liaison between the customer and the company, so the relationship can be well maintained. Customer satisfaction towards services obtained during the conduct of business transactions will have a positive impact for the company, as this can make the customers stay loyal to the company, as well as company profit can be increased as increasing customer loyalty.